Factors associated with 30-day readmissions following medical hospitalizations among Medicaid beneficiaries with schizophrenia, bipolar disorder, and major depressive disorder. (September 2020) - Cook, Judith A.; Burke-Miller, Jane K.; Jonikas, Jessica A.; Aranda, Frances; Santos, Alberto
Highlights: Adults with serious mental illness have an elevated rate of 30-day readmissions after medical hospitalizations, but little is known about the differential experiences of people with schizophrenia, bipolar disorder, and major depression. In a multivariable analysis, compared to those with no SMI, people with schizophrenia had the highest odds of 30-day readmission, followed by those with bipolar disorder, and those with major depressive disorder. Readmissions also were more likely among those with substance use disorders, males, those with Medicaid eligibility due to disability, patients with longer index hospitalizations, and those with 2 or more medical co-morbidities. The study's findings can be used to design transition interventions and service delivery systems that address the complex needs of people with schizophrenia and co-occurring medical conditions. Abstract: While evidence suggests that adults with serious mental illness have an elevated rate of 30-day readmissions after medical hospitalizations, most studies are of patients who are privately insured or Medicare beneficiaries, and little is known about the differential experiences of people with schizophrenia, bipolar disorder, and major depression. We used the Truven Health Analytics MarketScan® Medicaid Multi-State Database to study 43, 817 Medicaid enrollees from 11 states, age 18-64, who were discharged from medical hospitalizations in 2011. Our outcome was unplanned all-cause readmissions within 30 days of discharge. In a multivariable analysis, compared to those with no SMI, people with schizophrenia had the highest odds of 30-day readmission (aOR: 1.46, 95% CI: 1.33-1.59), followed by those with bipolar disorder (aOR: 1.25, 95% CI: 1.14-1.38), and those with major depressive disorder (aOR: 1.18, 95% CI: 1.06-1.30). Readmissions also were more likely among those with substance use disorders, males, those with Medicaid eligibility due to disability, patients with longer index hospitalizations, and those with 2 or more medical co-morbidities. This is the first large-scale study to demonstrate the elevated risk of hospital readmission among low-income, working-age adults with schizophrenia. Given their greater psychological, social, and economic vulnerability, our findings can be used to design transition interventions and service delivery systems that address their complex needs.